Dynamic fault tree analysis based on Petri nets - Xiaojie Zhang; Qiang Miao; Xianfeng Fan; Dong Wang (2009 8th International Conference on Reliability, Maintainability and Safety, 2009)
In traditional dynamical fault tree analysis, it is necessary to modularize DFT tree firstly so as to obtain static subtrees and dynamic subtrees. Generally, binary decision diagram (BDD) and Markov chains are utilized in the DFT to process static and dynamic subtrees, respectively. However, due to the possibility of state combinatorial explosion problem in Markov chain, it is difficult to analyze system with DFT in some cases. This paper investigated Petri net method in DFT in order to solve this problem. An example of processor system is analyzed with the proposed Petri net based DFT, which contains many dynamic logic gates in two classes. The analysis results show that the proposed method can overcome the state combinatorial explosion problem and guarantee high accuracy.